Description of the Personal Hygiene of Women Adolescent in the At-Tin Orphanage - Kurnia Sari Hayon; Deviarbi Sakke Tira; Amelya Sir (Lontar : Journal of Community Health, 2023)
The transition period from childhood to adulthood marked by accelerated physical, mental, emotional, and social development in a dynamic phase of growth and development in life is the understanding of adolescence. Adolescence is the age of puberty, so it is related to reproductive health. Health problems due to insufficient knowledge about personal hygiene in the reproductive organs are reproductive health problems, such as cervical cancer, vaginal discharge, genital skin irritation, allergies, and urinary tract infections. This study aims to describe personal hygiene in adolescents at the At-Tin Orphanage, Kupang City, in 2021. This type of research is quantitative, using a descriptive method. The population in this study amounted to respondents using total sampling. Analysis of the data used in this study is descriptive statistics. Data was collected using observation sheets and questionnaire sheets. The results showed that adolescents' knowledge about personal hygiene was good (62.2%), adolescent attitudes about personal hygiene were negative (86.7%), adolescent behavior about personal hygiene was good (73.3%), and facilities and infrastructure regarding personal hygiene were available (100%). The caretakers at the At-Tin orphanage need to carry out routine supervision to check or supervise the cleanliness of the rooms and personal hygiene of respondents so that young women can maintain the cleanliness of their rooms and themselves properly to avoid various diseases.